Physical and Ecological Impacts of Climate Change on Indian Economy - Dr. Sanjay Shahi (International Journal of Engineering and Management Research, 2020)
Every country on every continent is now affected by climate change. People, communities, and countries are paying a high price for it today, and it will get worse in the future. People are already feeling the effects of climate change, which include shifting weather patterns, increasing sea levels, and an increase in the frequency and intensity of extreme weather events. More than any other group, those in need are being impacted the worst.